ChemInform Abstract: Synthesis of Oxindolyl Pyrazolines and 3‐Amino Oxindole Building Blocks via a Nitrile Imine [3 + 2] Cycloaddition Strategy. Issue 10 (7th March 2013) - Singh, Anand; Loomer, Amanda L.; Roth, Gregory P.
Abstract Treatment of 3‐alkylidene oxindoles with nitrile imines generated in situ allows an efficient, regio‐, and stereoselective access to novel spirocyclic pyrazolines like (III), (VI), and (XIII).